The Comparison of the Microbiological Characteristics of Wet Dough and Dry Powder Tarhana’s and Evaluation of Possible Health Risks - İçli, Nesrin; Kesbiç, Fevziye Işıl (Turkish Science and Technology Publishing (TURSTEP), 2021)
Tarhana is a traditional food produced by different traditional methods and the materials used in production are changing from a region to another region. The total yeast and molds, total mesophilic aerobic bacteria, Escherichia Coli and enterococci bacteria count of wet dough Kastamonu tarhana and dry powdered tarhana samples were investigated in this study. All microorganisms examined in our study were detected in one of the wet dough tarhana samples. The highest total yeast and molds, total mesophilic aerobic bacteria, Escherichia coli and enterococci bacteria counts were determined for the wet dough tarhana samples to be 2.2×106, 6.6×107, 1.2×106 and 1.9×106 cfu/g, respectively. No growth of microorganism capable of reproduction was observed in the powdered tarhana produced industrially. In addition, the Escherichia coli and enterococci bacteria were not detected for any of the dry powder tarhana samples. It was seen that the microbial load of the wet tarhana produced at home in Kastamonu was higher than the powdered tarhana. The reason for this situation was thought to be due to poor production and hygiene conditions. The presence of Escherichia coli and enterococci bacteria in samples indicates that there is possible fecal contamination of the raw materials used in wet dough tarhana production. Electron microscope images of molds obtained in our study are similar to molds producing mycotoxins. These results show that the wet dough tarhana have a greater risk for microorganism development and human health compared to dry powder tarhana.
Keywords: S; Agriculture (General); mold; Agriculture; tarhana; mycotoxin; S1-972; sem; pathogen bacteria; 2. Zero hunger; 3. Good health